SOSIALISASI PENERAPAN COMMUNITY BASED ECOUTOURISM DALAM MENDUKUNG PENGEMBANGAN OBJEK AGROWISATA DI NEGERI SOYA - Latupapua, Yosevita Th.; Tuhumuri, Andri; Latupeirissa, Yerri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
The community service activity was carried out as an effort to enhance understanding of the development of the 3A components in supporting the potential of dusung as an agrotourism attraction in Negeri Soya. The understanding and involvement of dusung owners and the local government play a crucial role in supporting the future development of this tourism asset. This community service activity aimed to increase the interest and understanding of dusung landowners and village officials in Soya Village in developing the natural resource potential within the dusung area as a Community-based ecotourism (CBE) agro-tourism destination. The methods used included socialization sessions, focus group discussions, and field observations. The activity was carried out over the course of one week and involved local community members and village authorities as participants in the community engagement program. The results showed a significant improvement in participants' understanding of the concepts of agro-tourism, the 3A components (Attraction, Accessibility, Amenities), CBE principles, and the impacts of tourism development. Pre-test and post-test results indicated an increase in comprehension, with approximately 90–98% improvement across all questions following the program's implementation.